Anmeldelser - Bergsagel, John (Danish Yearbook of Musicology, 2005)
Review of: Michael Chesnutt: The Medieval Danish Liturgy of St Knud Lavard (repr. from Opuscula, xi, ed. Britta Olrik Frederiksen. Bibliotheca Arnamagnæana, 42, Copenhagen 2003); Copenhagen: C.A. Reitzel, 2003.